A collaborative cardiologist-pharmacist care model to improve hypertension management in patients with or at high risk for cardiovascular disease - Irons BK; Meyerrose G; Laguardia S; Hazel K; Seifert CF (Centro de Investigaciones y Publicaciones Farmaceuticas, 2012)
Physician led collaborative drug therapy management utilizing clinical pharmacists to aid in the medication management of patients with hypertension has been shown to improve blood pressure control. With recommendations for lower blood pressures in patients with coronary artery disease, a cardiologist-pharmacist collaborative care model may be a novel way to achieve these more rigorous goals of therapy. Objective: The purpose of this project was to evaluate this type of care model in a high cardiac risk patient population. Methods: A retrospective cohort study determined the ability of a cardiologist-pharmacist care model (n=59) to lower blood pressure and achieve blood pressure goals (< 130/80 mmHg) in patients with or at high risk for coronary artery disease compared to usual cardiologist care (n=58) in the same clinical setting. Results: The cardiologist-pharmacist care model showed a higher percentage of patients obtaining their goal blood pressure compared to cardiologist care alone, 49.2% versus 31.0% respectively, p=0.0456. Greater reductions in systolic blood pressure (-22 mmHg versus -12 mmHg, p=0.0077) and pulse pressure (-15 mmHg versus -7 mmHg, p=0.0153) were noted in the cardiologist-pharmacist care model. No differences in diastolic blood pressure were found. There was a shorter duration of clinic follow-up (7.0 versus 13.2 months, p=0.0013) but a higher frequency of clinic visits (10.7 versus 3.45, p<0.0001) in the cardiologist-pharmacist care model compared to usual care. The number of antihypertensive agents used did not change over the time period evaluated. Conclusion: This study suggests a team-based approach to hypertensive care using a collaborative cardiologist-pharmacist care model improves blood pressure from baseline in a high cardiac risk patient population and was more likely to obtain more stringent blood pressure goals than usual care.